(untitled) (Advancements in Homeopathic Research, 2022)
The incidence of haemorhoids is increasing due to changing lifestyle and irregular bowel habits. The initial signs of haemorhoids should be recognized so that disease can be brought under control at an early stage with minimum treatment with homoeopathy and hence we can avoid surgery. Many cases which are referred surgery are well managed with homoeopathic medicines.